The Role of Online Communication Platforms in Maintaining Social Connectedness When Face-to-face Communication is Restricted - Gülnur Yenilmez Kaçar (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Social connectedness, an indicator of psychological well-being, requires social interaction and communication among individuals. Prior research usually examined the relationship between the use of online communication channels and the sense of social connectedness under the circumstances where face-to-face communication was readily available. Pandemic provided an excellent setting to study the sole effect of the use of online communication on social connectedness as online communication was not accompanied by in-person communication due to restrictions such as lockdowns. Seizing the opportunity, this study aims at investigating the relationship between the use of online communication platforms and social connectedness at a time when face-to-face communication was not an option and individuals employed online communication channels heavily. To this end, a survey was conducted online on 406 college students in Turkey in November- December 2022 to present retrospective analyses. The findings indicate while face-to-face communication is the prime component to build social connectedness, the use of online communication channels, particularly WhatsApp, social networking sites, video call helped to maintain social bonds among individuals when in-person communication was virtually absent. The research provides insights on how different communication channels can promote social connectedness with varying degrees depending on their social presence.